Close Echoes : Public Body & Artificial Space. - Aigner, Carl; Bussel, David; Denk, Wolfgang; Fatka, Jaroslav; Kampl, Gudrun; Malá, Olga; Musgrave, David; Schöllhammer, Georg; Srp, Karel; Kunsthalle Krems (Praha : Prague City Gallery, 1998)
Billingham, Richard ; Bitter, Sabine ; Borland, Christine ; Bromová, Veronika ; Chapman, Dinos & Jake ; Collishaw, Mat ; Evans, Cerith Wyn ; Frankland, John ; Gordon, Douglas ; Hartley, Alex ; Hatoum, Mona ; Jasanský, Lukás ; Kampl, Gudrun ; Krystufek, Elke ; Lane, Abigail ; Moscouw, Micheala ; Othová, Markéta ; Polák, Martin ; Prihoda, Jiri ; Taylor-Wood, Sam ; Vincourova, Katerina ; Weber, Helmut
biog., ind. tent., gr. tent., prijzen, coll....[21 p.]
Tsjechisch & Engels & Duits
Close Echoes : Public Body & Artificial Space,Galerie hlavniho mesta Prahy (Prague City Gallery), Praha, 6.3. - 31.5.1998 / Kunsthalle Krems, 20.9. - 22.11.1998
boek
Keywords: Groot-Brittannië; Oostenrijk; Tsjechië